An improvement on the gas transfer velocity model with application to scatterometer data - Fabio Lekecinskas Augusto (2015)
The increase of carbon dioxide in the atmosphere observed in recent decades is causing the acidification of the oceans besides the global warming. The amount of carbon dioxide that crosses the air-sea interface is not well known because this amount depends upon the partial pressure of carbon dioxide and the gas transfer velocity. The gas transfer velocity is a variable based on Fick\'s Law of Diffusion and is normally parametrized as a function of wind velocity at the height of 10 meters. However, the result of this parametrization have errors greater than 100%. Newer parametrization include the effects of temperature, friction velocity and the presence of surface waves. Based on the simplest model of air-sea gas transfer model, the stagnant film theory, this study developed a methodology to improve the knowledge of the relation between the gas transfer velocity and the mean square slope. This variable accounts for the mean curvature of the waves in the surface. The data used was gathered within the scope of the DOGEE project in 2007. In that, a drifting buoy measured several parameters relative to the waves and the gas transfer velocity. The results show that the mean square slope calculated with waves whose wavenumber is between 40 and 50 radians per meter has the lowest root mean square errors of the regression between the mean square slope and the gas transfer velocity. This result showed to be very consistent when applied to the QuikSCAT scatterometer data and compared to a recent published study.